Components of value-semantic sphere of personality as predictors of migration intentions among the youth (on the example of Komsomolsk-on-Amur) - Bakina, A.V.; Orlova, O.A.; Yaremtchuk, S.V. (Socialʹnaâ Psihologiâ i Obŝestvo, 2019)
The article is devoted to the study of migration intentions among young people in Komsomolsk-on-Amur. The study tested two hypotheses: 1) differences between groups of young people with different migration activity will be manifested in the mismatch between values and their accessibility, as well as in the level of subjective well-being; 2) components of the value-semantic sphere are predictors of migration intentions among young people. The sample group included 130 subjects aged 16—25 years (mean age 23.1 years). To explore value-semantic sphere was used the methodology of E.B. Fantalova “level of correlation between “value” and “accessibility” in various spheres of life” and the Index of personal well-being. The results of the study showed that 26% of young people are not going to change their place of residence, 22% — are going to leave the city. Step-by-step regression analysis allowed us to identify explanatory models that predict the migration activity of young people. Subjective well-being is the most significant predictor of migration intentions (28% of variance). The second place is occupied by the sharpness of the mismatch between the importance of values and their subjective accessibility (26% of the variance). Статья посвящена исследованию миграционных намерений молодежи города Комсомольска-на-Амуре. В исследовании проверялись две гипотезы: 1) различия между группами молодежи с разной миграционной активностью будут проявляться в рассогласовании между ценностями и их доступностью, а также в уровне субъективного благополучия; 2) компоненты ценностно-смысловой сферы выступают предикторами миграционных намерений молодежи. В выборку вошли 130 испытуемых в возрасте 16—25 лет (средний возраст — 23,1 года). Для изучения ценностно-смысловой сферы использовались методики «Уровень соотношения «ценности» и «доступности» в различных жизненных сферах» Е.Б. Фанталовой и «Индекс персонального благополучия». Результаты исследования показали, что 26% молодых людей не собираются менять место жительства, 22% — намерены уехать из города. Пошаговый регрессионный анализ позволил выделить объяснительные модели, предсказывающие миграционную активность молодежи. Субъективное благополучие является наиболее значимым предиктором миграционных намерений (28% дисперсии). На втором месте оказалась острота рассогласования между важностью ценностей и их субъективной доступностью (26% дисперсии).